Sistem Pendukung Keputusan Pemilihan Hotel Terbaik dengan Menggunakan Metode Simple Additive Weighting (SAW) - Manalu, Hardi Giat Sofian; Tarigan, Safrin Zulkarnain; Batubara, Gunawan; Mesran, Mesran; Lubis, Ridha Maya Faza (Graha Mitra Edukasi, 2025)
The booming tourism sector offers travellers many accommodation options. However, this diversity can make it difficult to find the right hotel. Therefore, to assist travellers in this difficult decision-making process, a Decision Support System (DSS) for Best Hotel Selection was created. This SPK uses a sophisticated algorithm called ‘method in use’, which can analyse hotel data in multiple dimensions. To make the best hotel recommendation, various factors are considered, including price, location, facilities, guest reviews, and travellers' personal preferences. Travellers get many great benefits from the application of this SPK, including, Time efficiency, Right decision and Better experience. This research uses the SAW method in making a decision in determining the best hotel. Based on the results of research using the SAW method, it can be concluded that this method is very helpful in the process of making hotel selection decisions in Dumai. By giving weight to each criterion that is considered important by users, such as price, location, and facilities, SAW produces a final value for each hotel alternative. Through this calculation, users can easily compare and choose the hotel that best suits their needs. In this study, Hotel C obtained the highest score of 0.850, followed by Hotel B and Hotel G with final results of 0.820 and 0.810 respectively